Radical cystectomy for bladder cancer: сomparison of early surgical complications during laparoscopic, open-access, and video-assisted surgery - A. K. Nosov (Onkourologiâ, 2015)
Objectives. To evaluate peri- and postoperative morbidity and functional results of LRC in a single-site cohort of patients, comparing it with standard open approach (ORC) and laparoscopic cystectomy with open urinary diversion (HALRC).Subjects and methods. A prospective analysis was performed in 51 muscle-invasive and locally advanced BCa patients who underwent RC between February 2012 and March 2014 in N. N. Petrov Research Institute of Oncology, Saint-Petersburg. The final cohort included 21 ORC, 21 LRC and 9 HALRC patients. Mean patients age was 64 (38–81) years old and did not differ in all groups. Pathological stage were similar in all groups. Multivariable logistic and median regression was performed to evaluate operating time, perioperative and postoperative complications (30-d and 90-d), readmission rates, length of stay (LOS) – totally and in ICU.Results. Operating time during LRC and HALRC was longer than that of ORC (398 min vs 468 min vs 243 min, respectively). Despite that, there was no statistically significant influence of type of surgery on intraoperative complications – 14.3 % in ORC group, 11.1 % in HALRC and 4.7 % in LRC patients. Major complication rates (Clavien grade  3; 23.8 % vs 33.3 % vs 19.4 %) were similar between all groups. However, LRC had 4,0 times lower rate of minor complications (Clavien grade 1–2) compared to ORC (4.7 % vs 19.0 %). LRC had a significantly shorter LOS (27.8 d vs 32.6 d vs 22.6 d in ORC, HALRC and LRC groups, respectively), but no significant differences in ICU stay existed (5.1 d vs 3.1 d vs 2.1 d). Morbidity were present by one patient in each group (medium rate 5,8 %). The common transfusion rate during and after surgical intervention was 19.6 % and was higher in ORC group (33.3 % vs 4.7 % in LRC); as well, intraoperative bleeding was lower in minimally invasive techniques – the average volume of blood loss was 285 ml in LRC and did not differ between HALRC and ORC groups – 468 and 577 ml, respectively. Depending on the timing of complications, there were 30-d complications in 19 patients (37,2 %) and 90-d in 27 (52,9 %). The greatest difference was observed between any grade gastrointectinal complications (foremost, ileus) with significantly better outcomes in LRC patients – 14.2 %, compared with 47.6 % and 55 % in ORC and HALRC, respectively.Conclusions. We found that LRC is safe and associated with lower blood loss, decreased postoperative ileus and lower LOS compared with ORC. Using a population-based cohort, we found that laparoscopic surgery for bladder cancer decreased minor complications (mainly due to lower bleeding and gastrointestinal complication rate) and had no impact on major complications.